Equality Clause in Pakistan: A Need for Elevation to Supra Constitutional Status - Quddus, Dr. Usman; Majid, Abdul; Khan, Muhammad Arif; Ahmad, Mushtaq; waheed, Abdul (The journal of contemporary issues in business and government, 2021)
Equality in all its manifestations is a notion that requires implementation in Pakistan in every facet being the premise idea for the founding of Pakistan. The purpose of this article is to highlight the importance of equality as the foundational feature of Pakistan and make out a case for its incorporation in the legal structure as supreme consideration. The methodology adopted is doctrinal and descriptive analysis of the issue in hand. The findings of research mandate revisions in constitution of Pakistan and legal paradigm of Pakistan with equality at the forefront. Such an analysis to authors knowledge has not been undertaken before.